MO( VI), MN(II) AND CR(III) IONS FROM THE COMPOSITION OF AN ARTIFICIAL MIXTURE - Sobirova Zilola Olimjon qizi (International Journal of Literature and Language Studies, 2026)
The study presents a selective sorption–photometric method for the determination of Mn(II), Mo(VI), and Cr(III) ions in complex food samples. Modified cellulose-based sorbents containing organic reagents were used for selective extraction and preconcentration of metal ions. The influence of interfering ions was investigated using synthetic mixtures, and the developed method demonstrated high selectivity, accuracy, and reproducibility. The proposed approach was successfully applied for the analysis of canned and food products, providing reliable determination of trace metal ions.